Правове регулювання гарантування міжнародної енергетичної безпеки під час збройних конфліктів - Кориневич, А. О.; Кориневич, А. О.; Korinevich, А. (My University, 2013)
The article is dedicated to international legal regulation of impact of armed conflicts on international energy security, in particular on security of energy installations and usage of natural resources during international and non-international armed conflicts. Provisions of treaties, customary international humanitarian law, and practice of International Court of Justice are analyzed in the article.
Кориневич А. О. Правове регулювання гарантування міжнародної енергетичної безпеки під час збройних конфліктів / А. О. Кориневич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 102-109.
Keywords: міжнародна енергетична безпека; міжнародна енергетична безпека під час збройних конфліктів; безпека енергетичних установок; використання природних ресурсів у міжнародних і неміжнародних збройних конфліктах; судова практика Міжнародного суду ООН з питань енергетичної безпеки; международная энергетическая безопасность; международная энергетическая безопасность во время вооруженных конфликтов; безопасность энергетических установок; использование природных ресурсов во время международных и немеждународных вооруженных конфликтов; судебная практика Международного суда ООН по вопросам энергетической безопасности; International Energy Security; international energy security during armed conflicts; the safety of power plants; use of natural resources in international and non-international armed conflicts; the jurisprudence of the International Court of Justice on energy security